Study of neutron-deficient isotopes of Fl in the 239Pu, 240Pu + 48Ca reactions. (July 2016) - Voinov, A A; Utyonkov, V K; Brewer, N T; Oganessian, Yu Ts; Rykaczewski, K P; Abdullin, F Sh; Dmitriev, S N; Grzywacz, R K; Itkis, M G; Miernik, K; Polyakov, A N; Roberto, J B; et al.
Abstract: The results of the experiments aimed at the synthesis of Fl isotopes in the 239 Pu + 48 Ca and 240 Pu + 48 Ca reactions are presented. The experiment was performed using the Dubna gas-filled recoil separator at the U400 cyclotron. In the 239 Pu+ 48 Ca experiment one decay of spontaneously fissioning 284 Fl was detected at 245-MeV beam energy. In the 240 Pu+ 48 Ca experiment three decay chains of 285 Fl were detected at 245 MeV and four decays were assigned to 284 Fl at the higher 48 Ca beam energy of 250 MeV. The α-decay energy of 285 Fl was measured for the first time and decay properties of its descendants 281 Cn, 277 Ds, 273 Hs, 269 Sg, and 265 Rf were determined more precisely. The cross section of the 239 Pu( 48 Ca, 3 n ) 284 Fl reaction was observed to be about 20 times lower than those predicted by theoretical models and 50 times less than the value measured in the 244Pu+ 48 Ca reaction. The cross sections of the 240 Pu( 48 Ca, 4-3 n ) 284, 285 Fl at both 48 Ca energies are similar and exceed that observed in the reaction with lighter isotope 239 Pu by a factor of 10. The decay properties of the synthesized nuclei and their production cross sections indicate rapid decrease of stability of superheavy nuclei with departing from the neutron number N=184 predicted to be the next magic number.